Autonomic neuropathy, cardivascular form - a risk factor for progression of complications of diabetes mellitus type 2 - Kurbanova, Nozima Sobirdjanovna; Ibragimov, Dilhush; Djurakulova, Mashhura; Ahadov, Abdulla; Himmatov, Adham (Science and Education, 2024)
The article gives information about autonomic neuropathy, cardivascular form - a risk factor for progression of complications of diabetes mellitus type 2.